Design and sizing photovoltaic system for DC air-conditioning - Shatri, C.; Ismail, Daut, Prof. Dr.; Muhammad Irwanto; Noor Syafawati, Ahmad; S. S., Saad; Khairul Anuar, Mohd Nor (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.